(3GddBdj GdaQjOI aj TQM GdbUjOIs - (3eMeO Hf GdMSf Hf eMeO Hf jhSa GdaGSj GdebQj CHhYHO Gddgs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf LeGYI ef GdbQGA GdeTJZdjf HbUjOI GdTjN CHj GdbGSe GdTGWHj QMeg Gddg SCdhfj Cf CTQMgG s
(3BNQgG (B:s
(3hgj PGJ Mdj aJCed PcQ Gddg CYde s
(3GdfSNI HgG MhGTs
(3fSNI Chdis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdbQGAGJ hGdJLhjOs